Analisis Psikologi dan Sosiologi Korban Perang dalam Cerpen Sarajevo’s Wombs And The Children Of Torns Karya Aiman Tashika - Heni Heni (Universitas Cokroaminoto Palopo, 2020)
The most essential thing that every human in the world has is freedom. With freedom humans can display their existence as a result of reason and character. Freedom is a source of individual freedom to develop and develop their potential. But often humans are shackled by their freedom or independence by others. Likewise a nation that changes colonialism will be deprived of its freedom. The colonizing nation would oppose imposing its authority on its colonial state. The occupation of the Serbs against the Sarajevo nation was one of the cruel forms of colonialism on earth. Serbia commits terror against the citizens of Sarajevo. One form of horrific terror is the rapes committed by the Serbian army on Muslim women in Sarajevo. Serbia considers rape terror as the most effective weapon to kill the people of Sarajevo. The women of Sarajevo war victims recovered from the trauma that had escaped. Many of the victims of rape gave birth to children of Serbian soldiers. On the contrary, those who oppose the atrocities of the Serb-Sarajevo war are not only women but also innocent children as a result of rape. The psychological and sociological influence was very much accepted by the victims at the end of colonialism. Although the war is over, these victims of rape terror support life with unforgettable dark shadows. Both the mother and the child will continue to be haunted by these bad memories. These children would be difficult to accept in the community because they thought the children of the colonizers. They will be ostracized in the association and of course will resolve social discomfort.